2022
DOI: 10.1002/smll.202201225
|View full text |Cite
|
Sign up to set email alerts
|

Human Endometrium‐Derived Adventitial Cell Spheroid‐Loaded Antimicrobial Microneedles for Uterine Regeneration

Abstract: Asherman's syndrome (AS) occurs as a consequence of severe damage to the endometrial basalis, usually leading to menstrual abnormalities, infertility, and recurrent miscarriage in women. Currently, human endometrium‐derived adventitial cells (En‐ADVs) are considered ideal seed cells with high pluripotency for regenerative medicine. However, critical issues such as noninvasive repair of tissues, targeting of native stem cells, and continuous action in the injured sites are not well resolved. Herein, En‐ADV sphe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 37 publications
0
9
0
Order By: Relevance
“… [ 152 ] Arrowhead needles: GelMA; Base: bottom layer was N-acryloyl glycinamide (NAGA), top layer was PEGMA Arrays: Height: 760 ​μm Shape: Arrowhead Strength: 0.2 ​N/needle bFGF The arrowhead needles allowed MNs steadily adhering to the tissues and released growth factors; Backing layer prevented tissue adhesions [ 153 ] GelMA, Arrays: Height: 600 ​μm Shape: conical Strength: 0.2 ​N/needle Lactoferrin, human endometrium-derived adventitial cells Cells could rapidly form more biologically active three-dimensional cell spheres within the micropores surrounding the needles. Lactoferrin inhibited bacterial infections [ 154 ] …”
Section: Mns For Istrmentioning
confidence: 99%
See 1 more Smart Citation
“… [ 152 ] Arrowhead needles: GelMA; Base: bottom layer was N-acryloyl glycinamide (NAGA), top layer was PEGMA Arrays: Height: 760 ​μm Shape: Arrowhead Strength: 0.2 ​N/needle bFGF The arrowhead needles allowed MNs steadily adhering to the tissues and released growth factors; Backing layer prevented tissue adhesions [ 153 ] GelMA, Arrays: Height: 600 ​μm Shape: conical Strength: 0.2 ​N/needle Lactoferrin, human endometrium-derived adventitial cells Cells could rapidly form more biologically active three-dimensional cell spheres within the micropores surrounding the needles. Lactoferrin inhibited bacterial infections [ 154 ] …”
Section: Mns For Istrmentioning
confidence: 99%
“…In another study, Ding et al. prepared a layered GelMA hydrogel MNs containing lactoferrin (LF) with anti-inflammatory activity and antibacterial properties and human endometrium-derived epithelial cells (En-ADVs) [ 154 ]. The study designed a series of micropores on MNs in which EnADVs could be cultured as three-dimensional (3D) cell spheres.…”
Section: Mns For Istrmentioning
confidence: 99%
“…[38] Li et al fabricated two-segment MNs with gelatin methacryloyl and lactoferrin for treating Asherman's syndrome due to their rapid degradation and satisfactory antimicrobial activities, and the MNs promoted the restoration of both normal morphology and reproductive function in the injured uterus. [86] Other applications…”
Section: Treatment For Uterine Diseasesmentioning
confidence: 99%
“…Moreover, novel multifunctional MN patches were designed and prepared by Zhu and Li et al, which were found to enhance endometrial repair in rats (Figure 11). 93,110 In comparison to dissociated cells, MSC cell spheroids had significant advantages of cell proliferation, cell differentiation, and cell migration. This study exhibited the extensive application prospects of cells and biomaterials in tissue repair.…”
Section: Enhanced Uterine Functionmentioning
confidence: 99%
“…(C and D) Design of multifunctional microneedle patch loaded with MSC. Reproduced with permission 110. Copyright 2022, John Wiley and Sons.ZHU ET AL.…”
mentioning
confidence: 99%